The effect of mazindol on growth hormone secretion in boys with Duchenne muscular dystrophy. Issue 12 (December 1988) - Coakley, J H; Moorcraft, J; Hipkin, L J; Smith, C S; Griffiths, R D; Edwards, R H
Abstract : Mazindol has been reported to improve muscle function in Duchenne muscular dystrophy (DMD) by virtue of its growth hormone (GH) suppression. The effects were studied on GH secretion (in response to growth hormone releasing factor and sleep) of mazindol 2 mg daily for 3 months in five boys with DMD. No consistent change was found following mazindol therapy. Adverse effects were noted in all the boys which may preclude long term use of mazindol in DMD.